PENINGKATAN MOTIVASI DAN HASIL BELAJAR PKN MELALUI MODEL PEMBELAJARAN OLIMPIADE BAGI SISWA KELAS VI SD NEGERI IV BATURETNO TAHUN 2015/2016 - Eko Hargito (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2020)
AbstractThe purpose of this study was to increase motivation and learning outcomes for Civics Education through the application of the Olympic Learning model to Grade VI students of SD Negeri IV Baturetno in the 2015/2016 academic year. The method used in this research is classroom action research conducted in 2 cycles. The action research steps taken in each cycle include 4 stages, namely: (1) planning, (2) implementing actions, (3) observations, and (4) evaluation-reflection. The results of this study are there is an increase in learning motivation Citizenship Education (PKn) which is in the minimum good category by 48% ie from 8 students (32%) in the pre cycle, in the first cycle to 13 students (52%) and in the second cycle to 20 students (80%) with an average student motivation of 84 or in the Good category (B). In addition, there was also an increase in Civics Education (PKn) learning outcomes from 9 students (36%) of students completing their studies in pre-cycle, to 19 students (76%) in cycle I, and in cycle II to 23 students (92% ). total increase of 52%. The average score of learning outcomes is increased by the pre-cycle average value of 66.8. , in the first cycle to 73.6, and in the second cycle to 83.2. So that the total increase in average learning outcomes of 16, 4.Keywords: Motivation, Learning Outcomes, Olympic Learning Model